Lignocellulosic biomass-driven biohydrogen production: Innovations, challenges, and future prospects for a sustainable green hydrogen economy - Raut S.S.; sharma A.; Mishra A. (My University, 2025)
Hydrogen (H2) is a clean and sustainable energy carrier that can help decrease dependence on fossil fuels. When produced from renewable or low-carbon sources, it can substantially lower greenhouse gas emissions by substituting conventional fossil fuel-based energy systems. H2 production, derived from renewable sources, offers a promising alternative to conventional H2 generation methods. This review provides a comprehensive overview of the various biological methods employed for H2 production, including dark fermentation, photofermentation, and biophotolysis. Each of these methods has distinct advantages and limitations in terms of efficiency, scalability, and operational conditions. A wide range of feedstocks has been explored for H2 production, including first-generation biomass, such as sugar- and starch-based crops, as well as second-generation lignocellulosic biomass, such as agricultural residues and organic waste. Factors such as pH, temperature, feedstock composition, microbial strains, and nutrient availability critically affect the H2 yield and production efficiency. Additionally, pretreatment methods for complex feedstocks are crucial for enhancing H2 yields by improving substrate accessibility for microbial conversion. The review also addresses the challenges of H2 storage and transport, which are critical for its integration into the energy economy. Advanced technologies for H2 storage, including compression, liquefaction, and chemical storage in metal hydrides and liquid organic H2 carriers (LOHCs), are discussed. The efficient and safe transport of H2 over long distances remains a key technical hurdle, necessitating innovations in pipeline infrastructure and storage materials. This review highlights recent advancements and ongoing research aimed at overcoming these challenges, ultimately contributing to the development of a sustainable H2 economy. © 2025 Hydrogen Energy Publications LLC